Tingkat Kesejahteraan Spiritual Anak Binaan LPKA I Tangerang - Ummah Karimah; Romlah Ghany; Wiwied Widiyanti; Azka Putra Prawira (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
Spiritual well-being itself has been recognized as the spiritual condition of individuals who feel their lives are good and can function optimally. Various studies have been conducted to reveal what factors can influence the level of spiritual well-being. Spiritual well-being in foster children can be a foundation for them in facing a critical and turbulent period at the completion of the sentence, because the problems faced in completing the sentence at LPKA can be felt increasingly concerning and transformed into critical personal problems because it has led to various forms of decline in the spiritual well-being of a foster child. Therefore, it is important to have happiness for foster children as an indicator of quality of life. The condition of spiritual well-being in foster children was assessed in terms of age, gender, socioeconomic status of parents, and intentional activities. The results of the study indicate that the average spiritual wellbeing is low and reveal that there are significant differences in the spiritual wellbeing of foster children in terms of gender, socioeconomic status of parents and involvement in intentional activities. The most influential dimension of spiritual well-being is usually found in environmental mastery, where children in the adolescent phase feel happy when they are able to master their environment well. The purpose of the research he conducted was to express the level of spiritual well-being of children fostered by LPKA I Tangerang. Thus, they can complete the period of serving their sentence in a timely manner. The stages of research methods through field research and descriptive qualitative approach by examining data in the form of scientific journals, books, and manuscripts. The results of this study are expected to have recommendations for higher education institutions, namely Islamic universities, especially in carrying out their duties as educational institutions that educate the lives of generations, require insight and knowledge related to aspects that can affect the development of students as individuals who continue to develop through the provision of lecture assignments not only in educational institutions but in correctional institutions so that students have new and many experiences and insights.